Intravenous augmentation treatment and lung density in severe α1 antitrypsin deficiency (RAPID): a randomised, double-blind, placebo-controlled trial - Chapman, Kenneth R; Burdon, Jonathan G W; Piitulainen, Eeva; Sandhaus, Robert A; Seersholm, Niels; Stocks, James M; Stoel, Berend C; Huang, Liping; Yao, Zhenling; Edelman, Jonathan M; McElvaney, Noel G (The Lancet (British edition), 2015)
The efficacy of α1 proteinase inhibitor (A1PI) augmentation treatment for α1 antitrypsin deficiency has not been substantiated by a randomised, placebo-controlled trial. CT-measured lung density is a more sensitive measure of disease progression in α1 antitrypsin deficiency emphysema than spirometry is, so we aimed to assess the efficacy of augmentation treatment with this measure. The RAPID study was a multicentre, double-blind, randomised, parallel-group, placebo-controlled trial of A1PI treatment in patients with α1 antitrypsin deficiency. We recruited eligible non-smokers (aged 18–65 years) in 28 international study centres in 13 countries if they had severe α1 antitrypsin deficiency (serum concentration <11 μM) with a forced expiratory volume in 1 s of 35–70% (predicted). We excluded patients if they had undergone, or were on the waiting list to undergo, lung transplantation, lobectomy, or lung volume-reduction surgery, or had selective IgA deficiency. We randomly assigned patients (1:1; done by Accovion) using a computerised pseudorandom number generator (block size of four) with centre stratification to receive A1PI intravenously 60 mg/kg per week or placebo for 24 months. All patients and study investigators (including those assessing outcomes) were unaware of treatment allocation throughout the study. Primary endpoints were CT lung density at total lung capacity (TLC) and functional residual capacity (FRC) combined, and the two separately, at 0, 3, 12, 21, and 24 months, analysed by modified intention to treat (patients needed at least one evaluable lung density measurement). This study is registered with ClinicalTrials.gov, number NCT00261833. A 2-year open-label extension study was also completed (NCT00670007). Between March 1, 2006, and Nov 3, 2010, we randomly allocated 93 (52%) patients A1PI and 87 (48%) placebo, analysing 92 in the A1PI group and 85 in the placebo group. The annual rate of lung density loss at TLC and FRC combined did not differ between groups (A1PI −1·50 g/L per year [SE 0·22]; placebo −2·12 g/L per year [0·24]; difference 0·62 g/L per year [95% CI −0·02 to 1·26], p=0·06). However, the annual rate of lung density loss at TLC alone was significantly less in patients in the A1PI group (−1·45 g/L per year [SE 0·23]) than in the placebo group (−2·19 g/L per year [0·25]; difference 0·74 g/L per year [95% CI 0·06–1·42], p=0·03), but was not at FRC alone (A1PI −1·54 g/L per year [0·24]; placebo −2·02 g/L per year [0·26]; difference 0·48 g/L per year [–0·22 to 1·18], p=0·18). Treatment-emergent adverse events were similar between groups, with 1298 occurring in 92 (99%) patients in the A1PI group and 1068 occuring in 86 (99%) in the placebo group. 71 severe treatment-emergent adverse events occurred in 25 (27%) patients in the A1PI group and 58 occurred in 27 (31%) in the placebo group. One treatment-emergent adverse event leading to withdrawal from the study occurred in one patient (1%) in the A1PI group and ten occurred in four (5%) in the placebo group. One death occurred in the A1PI group (respiratory failure) and three occurred in the placebo group (sepsis, pneumonia, and metastatic breast cancer). Measurement of lung density with CT at TLC alone provides evidence that purified A1PI augmentation slows progression of emphysema, a finding that could not be substantiated by lung density measurement at FRC alone or by the two measurements combined. These findings should prompt consideration of augmentation treatment to preserve lung parenchyma in individuals with emphysema secondary to severe α1 antitrypsin deficiency. CSL Behring.